2014
DOI: 10.2174/1872214807666140107151023
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Asthma

Abstract: Metabolic syndrome (MetS) is a syndrome that involves at least three disorders dyslipidemia, insulin resistance, obesity and/or hypertension. MetS has been associated with several chronic diseases in the adulthood; however, in the recent years, the syndrome was redefined in children. Girls with early menarche and asthma, and children with MetS and asthma that reach adulthood appear to have higher risk to develop severe or difficult to control asthma and a higher probability to suffer cardiovascular diseases. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 113 publications
1
21
0
Order By: Relevance
“…FGF21, a novel hormone partnering with insulin in regulation of glucose homeostasis, also signals through FGFR1 and FGFR2 . In support of our findings, previous studies have reported insulin resistance in children and adults with asthma, and an association of asthma with prediabetes and metabolic syndrome . Moreover, our validation experiments inducing loss of differentiation in epithelial cells by depriving them of insulin (which is long established as a necessary component in commercial culture of primary epithelium) demonstrate remarkable potential for insulin deficiency to induce epithelial genes and phenotypes consistent with those observed in asthma, including upregulation of “Th2‐high” markers and loss of competent barrier state.…”
Section: Discussionsupporting
confidence: 88%
“…FGF21, a novel hormone partnering with insulin in regulation of glucose homeostasis, also signals through FGFR1 and FGFR2 . In support of our findings, previous studies have reported insulin resistance in children and adults with asthma, and an association of asthma with prediabetes and metabolic syndrome . Moreover, our validation experiments inducing loss of differentiation in epithelial cells by depriving them of insulin (which is long established as a necessary component in commercial culture of primary epithelium) demonstrate remarkable potential for insulin deficiency to induce epithelial genes and phenotypes consistent with those observed in asthma, including upregulation of “Th2‐high” markers and loss of competent barrier state.…”
Section: Discussionsupporting
confidence: 88%
“…Several studies report insulin resistance in children and adults with asthma 93, 94 , as well as association of asthma and atopic eczema with pre-diabetes and metabolic syndrome 95 . We found profound changes in serum hormonal profiles of pre-pubertal non-obese allergic children compared to non-allergic controls, as well as chronic rhinosinusitis patients compared to healthy controls, including decreased levels in serum insulin and increased output of thyroid and growth hormones 96 .…”
Section: Mechanisms Of Barrier Defectsmentioning
confidence: 99%
“…14 Indeed, it has been shown that the markers of metabolic syndrome such as hypertension, hyperlipidemia, and insulin resistance can be associated with obesity and asthma. 15 Several human studies have reported that increased insulin level and insulin resistance were related to reduced lung function and increased AHR through several mechanisms such as airway smooth muscle proliferation and epithelial damage. 16 In this regard, metabolic syndrome has been shown to worsen asthma control and may have an impact on the treatment process in patients with asthma, 17 especially women.…”
Section: Introductionmentioning
confidence: 99%